PELATIHAN AKUPRESUR TELAPAK KAKI PADA PENDERITA DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS SUNGAI IYU ACEH TAMIANG TAHUN 2024 - Hayani, Nora; Zulkarnaini, Zulkarnaini; Sulistiany, Eva; Elfida, Elfida; Arbaiyah, Arbaiyah; Zakirullah, Zakirullah; Helmi, Alfian (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
If diabetes mellitus sufferers are not treated properly, it will result in various serious complications, including damage to the nervous system, apart from that, there are also complications that can cause numbness in the soles of the feet, called peripheral neuropathy, which can cause a decrease in foot sensitivity which can result in ulcers. The aim of training on foot acupressure for diabetes mellitus families is to increase the knowledge, skills and ability of families to care for family members independently towards increased sensitivity of the feet of diabetic sufferers. Participants in this activity were 30 families of diabetes mellitus sufferers in the Sungai Iyu Aceh Tamiang Health Center working area. This community service method is first a pre-test before conducting counseling, acupressure training and a post-test. The results obtained were an increase in knowledge, namely before the counseling the majority of participants' knowledge was 18 people (60%) after the counseling the majority became good 26 people (86.7%), as well as the ability to do acupressure from not knowing at all to being able by 19 people ( 63.3%) Routine training is needed for families of diabetes mellitus sufferers so that they can do it independently to prevent diabetic foot complications so as to increase foot sensitivity and reduce dependence on the use of pharmacological therapy